Structural performance deterioration of corroding reinforced concrete columns in marine environments - Chen, Hua-Peng; Jiang, Yu; Markou, George (My University, 2022)
In aggressive marine environments, rebar corrosion caused by chloride ion ingression in concrete is a critical factor leading to premature failure of in-service reinforced concrete (RC) structures. This paper investigated the structural performance deterioration of marine RC structures affected by rebar corrosion, and proposed new analytical models for predicting the residual bearing capacity of the corroded RC columns. By analyzing the performance deterioration mechanisms of the corroded RC structures, the material degradation models and structural strength reduction models were constructed. Then, the analytical models for estimating the residual bearing capacity of the corroded RC columns under various loading conditions were proposed. From the proposed models, the moment-axial force (M-N) interaction diagrams were plotted for analyzing the influence of corrosion damage locations on the residual bearing capacity. Furthermore, the impact of marine environmental factors on the service life of the corroding RC columns under various loading conditions was investigated. Finally, a numerical example for the corroded RC columns was given to demonstrate the effectiveness of the proposed models. The results showed that the residual bearing capacity of the marine RC columns can be significantly affected by the rebar corrosion level, corrosion damage location, load condition and in-service environment.
Keywords: Marine RC structure; Rebar corrosion; Concrete cracking; Residual bearing capacity; Remaining service life